2011
DOI: 10.1038/oby.2010.180
|View full text |Cite
|
Sign up to set email alerts
|

MC4R Variant Is Associated With BMI but Not Response to Resistance Training in Young Females

Abstract: Recently, a genome-wide association study (GWAS) that identified eight single-nucleotide polymorphisms (SNPs) associated with BMI highlighted a possible neuronal influence on the development of obesity. We hypothesized these SNPs would govern the response of BMI and subcutaneous fat to resistance training in young individuals (age = 24 years). We genotyped the eight GWAS-identified SNPs in the article by Willer et al. in a cohort (n = 796) that undertook a 12-week resistance-training program. Females with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…Similarly, another FAMuSS study from our research consortium reported PPARα L162V associated with the subcutaneous fat response to RT, with men carrying the rare allele gained considerably greater adiposity following unilateral resistance arm (Uthurralt et al 2007). Our previous reports (Orkunoglu-Suer et al 2011; Uthurralt, Gordish-Dressman, Bradbury, Tesi-Rocha, Devaney, Harmon, Reeves, Brandoli, Hansen, Seip, Thompson, Price, Angelopoulos, Clarkson, Moyna, Pescatello, Visich, Zoeller, Gordon, and Hoffman 2007) in combination with the present findings suggest that an interaction may exist between genetic profile and the body composition response to RT. Individuals who RT, with a certain genetic profile, may lead to poorer body composition response outcomes and limited localized exercise may trigger an increase in adiposity.…”
Section: 1 Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly, another FAMuSS study from our research consortium reported PPARα L162V associated with the subcutaneous fat response to RT, with men carrying the rare allele gained considerably greater adiposity following unilateral resistance arm (Uthurralt et al 2007). Our previous reports (Orkunoglu-Suer et al 2011; Uthurralt, Gordish-Dressman, Bradbury, Tesi-Rocha, Devaney, Harmon, Reeves, Brandoli, Hansen, Seip, Thompson, Price, Angelopoulos, Clarkson, Moyna, Pescatello, Visich, Zoeller, Gordon, and Hoffman 2007) in combination with the present findings suggest that an interaction may exist between genetic profile and the body composition response to RT. Individuals who RT, with a certain genetic profile, may lead to poorer body composition response outcomes and limited localized exercise may trigger an increase in adiposity.…”
Section: 1 Discussionsupporting
confidence: 84%
“…Our research group has observed that a missense mutation in the SH2b1 gene (rs7498665) resulted in women with the rare allele gaining more subcutaneous fat than women with two copies of the common allele (Orkunoglu-Suer et al 2010). Similarly, another FAMuSS study from our research consortium reported PPARα L162V associated with the subcutaneous fat response to RT, with men carrying the rare allele gained considerably greater adiposity following unilateral resistance arm (Uthurralt et al 2007).…”
Section: 1 Discussionmentioning
confidence: 99%
“…The limbic system is implicated in the control of food procurement as an evolutionarily conserved survival mechanism to defend against famine [36]. In this regard, these three GIANT consortium identified GWAS obesity SNPs that we found to be associated with physical activity and Orkunoglu-Suer et al found to be associated with body composition phenotypes [20] have been classified as hyperphagic genes related to appetite suppression and satiety whose regulation resides in the dopaminergic projection from the limbic system [37][38][39]. Recent research in animals suggests that the 'pleasure-reward' system residing in the dopaminergic pathway that regulates appetite and satiety has a key role in voluntary movement [25,40] and heightened reward sensitivity in animals with obesity that binge eat [41,42].…”
Section: Discussionmentioning
confidence: 77%
“…The sample consisted of healthy, young EuropeanAmerican men and women (Table 2) with a BMI level that reflected the larger FAMuSS cohort [20,26], and the general age-matched population from which they were recruited [1]. While age did not differ by sex (p > 0.05), men had a higher BMI than women (p < 0.001).…”
Section: Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation